Environmental life cycle impacts of small wastewater treatment plants: Design recommendations for impact mitigation. (1st December 2021) - Pham, Andrew; Moussavi, Sussan; Thompson, Matthew; Dvorak, Bruce
Highlights: Life-Cycle assessment used to evaluate 9 small wastewater treatment plants. Minimizing non-process facility area can reduce piping inventory and impact. Using Poly-vinyl chloride instead of ductile iron piping reduces impacts in 8 of 10 categories. Reducing overdesign can mitigate construction inventory and lifetime electric use. Abstract: The objective of this study was to quantify potential mitigation of environmental impacts from the operation and construction of wastewater treatment plants (WWTP) from implementing specific design recommendations. The study investigated small WWTPs, many of which are serving slow growing or declining populations. Life Cycle Assessment methodology was used to evaluate and compare the inventory and environmental impacts of nine small WWTP case studies. Detailed inventory data was collected from the facilities' engineering design plans and utility bills. One recommended practice was to avoid significant overdesign by planning for no lower than a 75% capacity utilization by the facilities' end-of-life. A theoretical correction to a 75% capacity utilization was estimated to mitigate 0.4% of lifetime electricity usage and 1% of secondary process concrete for every 1% reduction in design average flow rate. Relatedly, a 0.4% mitigation in the Carcinogenic and Global Warming impacts could be achieved for every 1% reduction in design average flow toward a 75% capacity utilization. Other suggested practices were focused on conveyance, namely, to minimize non-process facility area and to use polyvinyl chloride pipe instead of ductile iron pipe where possible. The latter practice was estimated to mitigate between 1.1 and 4.8% of the Carcinogenic impact in the nine case studies. Graphical abstract: Image, graphical abstract